Enterococcus durans EP1 a Promising Anti-inflammatory Probiotic Able to Stimulate sIgA and to Increase Faecalibacterium prausnitzii Abundance - Carasi, Paula; Racedo, Silvia María; Jacquot, Claudine; Elie, Anne Marie; Serradell, María de los Ángeles; Urdaci, María C. (Frontiers in Immunology, 2017)
Enterococcus species, principally E. faecium are used as probiotics since a long time with preference in animal applications but safety considerations were updated and also new uses as probiotics can be envisaged. Fifteen Enterococcus strains isolated from different foods were identified and analyzed for virulence factors and antibiotic resistance. Three Enterococcus durans strains were selected to study their immunomodulatory properties on PBMC and Caco2 cells. Two strains presented a profile towards a mild inflammatory Th1 response considering TNFα/IL10 and IL1β/IL10 cytokines ratios. The third strain EP1, presented an anti-inflammatory potential and was selected for in vivo studies. In mice, the strain was well tolerated and did not cause any adverse effects. EP1 administration increased the amount of IgA+ cells in mesenteric lymph node (MLN) after seven days of administration. In fecal samples, the IgA contents increased gradually and significantly from day 7 to day 21 in treated group. Additionally, IL-17, IL-6, IL-1b, IFN-γ and CXCL1 gene expression significantly decreased on day 21 in Peyer’s patches and IL-17 decreased in MLN. Mice treated with the probiotic showed significant lower mRNA levels of pro-inflammatory cytokines and mucins in the ileum at day 7 while their expression was normalized at day 21. Colonic expression of il-1β, il6 and mucins remain diminished at day 21. Ileum and colon explants from treated mice stimulated in vitro with LPS showed a significant reduction in IL-6 and an increase in IL-10 secretion suggesting an in vivo protective effect of the probiotic treatment against a proinflammatory stimulus. Interestingly, analysis of feces microbiota demonstrated that EP1 administration increase the amount of Faecalibacterium prauznitzii, a butyrate-producing bacteria, which is known for its anti-inflammatory effects. In conclusion, we demonstrated that EP1 strain is a strong sIgA inducer and possess mucosal anti-inflammatory properties. This strain also modulates gut microbiota increasing F. prausnitzii, a functionally important bacterium. Thus, E. durans EP1 is not only a good candidate to increases F. prausnitzii in some cases of dysbiosis but can also be interesting in gut inflammatory disorders therapy.